Mortality Analysis During July & September 2022 At Benazir Bhutto Hospital Rawalpindi: Mortality Analysis at Benazir Bhutto Hospital Rawalpindi - Shahid, Rizwana; Khan, Sadia; Khalid, Rabbia; Umar, Muhammad; Abdul Rehman, Shaikh; Zaidi, Nargis (Pakistan Journal of Health Sciences, 2022)
Hospital mortality reflects the quality of healthcare and is a tool to perceive department-wise variations in health care services. Objectives: To determine age, gender and department-wise mortality reported during July and September 2022 at Benazir Bhutto Hospital Rawalpindi. Methods: A cross-sectional descriptive study was done to analyse the variations in age, sex and department-wise in-hospital mortality among reported deaths at Benazir Bhutto Hospital (BBH) Rawalpindi during July and September 2022. The data were gathered from Hospital administration through informed consent. The demographics and primary cause of mortality were scrutinized. Data were analysed by using SPSS version 25.0 and Microsoft Excel 2010. Hospital death rate during July and September 2022 were computed. Difference in mean age of the expired cases other than those of infant and neonates was statistically determined by independent sample t-test. P < 0.05 was considered significant. Results: Of the total 5338 and 4514 patients admitted at BBH during July and September 2022, about 8.2% and 7.1% deaths were reported respectively. On an average 53.2% males and 46.8% females succumbed to various diseases. About 58.5% and 64.2% deaths were reported from Paediatrics department during July and September 2022 respectively. Around 45.6% neonatal deaths were reported during two months’ period. Difference in mean age of expired cases excluding infants and neonates was statistically insignificant (P=0.09). Infants and neonates frequently succumbed to sepsis, low birth weight, birth asphyxia and pneumonia. Conclusion: Infants and neonates are more susceptible to in-hospital mortality predominantly due to sepsis and low birth weight.